A study of factors that influence the effectiveness of 5S practice by Jabatan Agama Islam Melaka (Jaim) / Muhammad Amin Abdul Monir - Abdul Monir, Muhammad Amin (Faculty of Business and Management, 2010)
5S is a process of work place organizational and housekeeping which is carried out gradually and systematically. The 5S Philosophy focuses on effective work place organization and standardized work procedures. 5S simplifies your work environment, reduces waste and non-value activity while improving quality efficiency and safety. This research is about a study of ‘Factors that influence the effectiveness of 5S practice by Jabatan Agama Islam Melaka (JAIM)’. Factors such as top management involvement, promotional campaign, keeping records, 5s training, evaluation of the stuff and maintaining the system have been identified in order to investigate wheter or no those factors have significant relationship with 5S effectiveness. The survey conducted at the Jabatan Agama Islam Melaka (JAIM). The sample size for this study is 100 respondents who been working at the Jabatan Agama Islam Melaka (JAIM). Data obtain using two methods that are primary and secondary data. Respondents are required to answer the questionnaire that include the statement regarding relationship between factors and 5s effectiveness towards the Jabatan Agama Islam Melaka (JAIM). Once the necessary data has been collected, the data will be analyzed and summarize in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 14.0 has been used to summarize the data. The results are in the form of reliability testing, frequency and regression analysis. Based on this research, the result indicates that there are significant relationship between all the factors with the 5S effectiveness which include top management involvement, promotional campaign, keeping records, 5s training, evaluation of the stuff and maintaining the system. In additional, based on the mean and standard deviation for each factor, the first rank that gives the highest significant level according to their relationship with 5S effectiveness is Maintaining the System. It is followed by the second rank which is the Evaluation of the Staffs followed the third rank is the 5S Training and the forth rank is the Keeping Records. For the second last rank is the Top Management Involvement and last on rank is Promotional Campaign.